Correlates of ant (Hymenoptera: Formicidae) and tree species diversity in Sri Lanka - Gunawardene, Nihara; Majer, Jonathan; Edirisinghe, J. (Eigentumer, Herausgeber, Verleger, 2012)
Variation in species diversity across a landscape can be attributed to a variety of spatial and temporal factors, as well as inter-specific interactions. In this study, ant species assemblages were investigated in relation to habitat heterogeneity and tree species assemblage in a lowland dipterocarp-dominated forest in Sri Lanka. We tested the hypothesis that ant species assemblages would follow the same patterns of distribution as tree species assemblages along a small elevational gradient. A total of 100 ground-dwelling ant species and 143 tree species were recorded in 0.6 ha. Forty percent of variation in the ant species assemblages could be attributed to variation in elevation and percent plant cover at ground level. Although tree species assemblages also responded strongly to changes in elevation, there was no significant relationship between ant and tree species diversity. In this particular forest, ant species responded to the same topographical variation as did tree species assemblages; however, the ant assemblages appear to be responding to plant structure at ground level rather than to tree species diversity per se. These results suggest that preserving topographical features in a landscape may enhance ant species diversity.